COVID-19, the global education project and technology: Disrupting priorities towards rethinking education - Charl Wolhuter; Lynette Jacobs (Research in Social Sciences and Technology- OpenED Network, 2021)
This paper argues that the arrival of the COVID-19 pandemic created a space to reconceptualise education and rethink priorities. Although no one will deny the devastating impact of the pandemic, humans have been able to continue with various projects, including the global education project, largely made possible through unprecedented technology advancement, as well as the uptake of technologies that advanced pre-COVID-19. In many ways, the clear distinction between human and technological (being non-human) practices has blurred to a point where the mere nature of human projects such as the global education project has become post-human. While different schools of thought on the nature of “post-human” exist, we use it to refer to what we are becoming together, a comprehension and awareness of the connectedness between humans and their natural and technological environment and the ethical concerns that come with it. COVID-19 provides an opportunity to reconsider the connectedness, complexities and dynamics of the world, and what we (humans, nature, Earth, technology) are becoming. Based on a literature survey and critical refection on the state of the global education expansion project at the time of the onset of the COVID-19 pandemic, we suggest the following changes to the ways quantity, quality and equality in education are conceptualised. The employment of technology should be added in the conceptualisation of input quality. Flexibility, support and connectedness should be built into the process quality equation. Most importantly, ecology should also be added as a product of education, and not merely a contextual influence in education.